2009
DOI: 10.1007/s00027-009-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

A flume experiment to examine underwater sound generation by flowing water

Abstract: The hydrogeomorphology and ecology of rivers and streams has been subject of intensive research for many decades. However, hydraulically-generated acoustics have been mostly neglected, even though this physical attribute is a robust signal in fluvial ecosystems. Physical generated underwater sound can be used to quantify hydro-geomorphic processes, to differentiate among aquatic habitat types, and it has implications on the behavior of organisms. In this study, acoustic signals were quantified in a flume by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 51 publications
(58 reference statements)
3
39
0
Order By: Relevance
“…Although turbulence‐induced noise is dependent on flow velocity (McEachern and Lauchle, , it also depends on bed roughness elements (Nezu and Nakagawa, ; Dey, ), and these are larger in steep channels, having hydraulically rough flows. Noises generated by surface waves have been shown to decrease with an increasing water depth‐to‐bed roughness ratio (Tonolla et al ., ). Indeed, a torrent is noisier than a large river.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although turbulence‐induced noise is dependent on flow velocity (McEachern and Lauchle, , it also depends on bed roughness elements (Nezu and Nakagawa, ; Dey, ), and these are larger in steep channels, having hydraulically rough flows. Noises generated by surface waves have been shown to decrease with an increasing water depth‐to‐bed roughness ratio (Tonolla et al ., ). Indeed, a torrent is noisier than a large river.…”
Section: Discussionmentioning
confidence: 99%
“…Physical processes involving monitoring techniques of SGN are illustrated in Figure 1. SGN measurements are signals composed of bedload noises that can be mixed with extraneous noise sources, such as rain impacts (Roth et al, 2016), turbulence-induced noises (Gimbert et al, 2014), sounds generated by surface waves (Tonolla et al, 2009), road traffic (Barrière, Oth, et al, 2015b) or fluvial traffic (Vračar and Mijić, 2011). When bedload noises are isolated by signal processing tools (Barrière, Oth, et al, 2015b;Geay et al, 2017), SGN signals can be used to infer information on bedload transport.…”
Section: Introductionmentioning
confidence: 99%
“…Sounds emitted by hydrological processes such as sediment transport and flow turbulence have specific acoustic signatures. These unique underwater soundscapes can be detected with hydrophone measurements both with laboratory experiments and large‐scale measurements in the field (Tonolla, Lorang, Heutschi, Gotschalk, & Tockner, ; Tonolla, Lorang, Heutschi, & Tockner, ). They provide measures of habitat characteristics across spatially continuous and heterogeneous environments of riverine floodplains.…”
Section: What Can Be Acoustically Monitored In Freshwater Environments?mentioning
confidence: 99%
“…The position of the 'noise window', an acoustic feature which is a quiet area of the spectrum, between high and low frequency noises, is of potential significance to many animals in rivers (Wysocki et al 2007;Tonolla et al 2009;2010). The noise window usually falls in the 100-300 Hz region and is dependent on environmental conditions, although the exact characteristics responsible for the position of this quiet window are unknown Tonolla et al 2010).…”
Section: Topography and Relative Submergencementioning
confidence: 99%
“…Tonolla et al (2009) identified a 'quiet zone' downstream from a hydraulic jump generated using an obstacle in a laboratory flume, which they hypothesised was due to the scattering of sound by bubbles from the jump. However, it is known that low frequency sounds are relatively unaffected by scattering and absorption in comparison to higher frequencies.…”
Section: Plunging Water and Bubblesmentioning
confidence: 99%